Blood Glucose Meter Buying Behavior of Diabetic Patients: Factors Influencing Purchase - Pan, Bai-ling; Pan, Yi-tong; Gao, Zu-hua; Tung, Tao-Hsin (Frontiers in Public Health, 2022)
Objective To understand the blood glucose meter buying behavior of type 2 diabetic patients with poor glycemic control (two or more HbA1c ≥ 8% during visits in one year) and identify factors influencing it. Methods A survey was conducted among 585 diabetic patients with poor glycemic control who were treated in the outpatient or inpatient clinics of the Department of Endocrinology, Taizhou Hospital, Zhejiang Province from June 2020 to May 2021. The questionnaire collected general information and clinical data, and assessed blood glucose meter buying behavior. Chi-square test was used to compare the essential characteristics and clinical data between buyers and non-buyers of blood glucose meters. Additionally, stepwise logistic regression was used to analyze the factors influencing purchase. Results Of the 585 questionnaires distributed, 527 (90.09%) valid questionnaires were collected. Of the 527 respondents, 285 (54.08%) had purchased blood glucose meters. Not receiving insulin therapy (OR: 1.77, 95% CI: 1.13–2.77) and unawareness of self-monitoring of blood glucose (OR: 19.46, 95% CI: 12.51–30.26) were risk factors for non-purchase. Conclusion There is a need to actively increase the purchase of glucose meters among diabetic patients, by educating them about the importance of self-monitoring of blood glucose.